Detection of erythropoietin misuse by the Athlete Biological Passport combined with reticulocyte percentage. Issue 10 (21st December 2015) - Bejder, Jacob; Aachmann‐Andersen, Niels Jacob; Bonne, Thomas Christian; Olsen, Niels Vidiendal; Nordsborg, Nikolai Baastrup
Abstract : The sensitivity of the adaptive model of the Athlete Biological Passport (ABP) and reticulocyte percentage (ret%) in detection of recombinant human erythropoietin (rHuEPO) misuse was evaluated using both a long‐term normal dose and a brief high dose treatment regime. Sixteen subjects received either 65 IU rHuEPO × kg ‐1 every second day for two weeks (normal‐dose), 390 IU rHuEPO × kg ‐1 on three consecutive days (high‐dose), or frequent placebo treatment for 13 days in a randomized, placebo‐controlled, double‐blind crossover design. Blood variables were measured 4, 11, and 25 days following treatment initiation. The ABP based on haemoglobin concentration ([Hb]) and OFF‐hr score ([Hb] – 60 × √ret%) yielded atypical profiles following both normal‐dose and high‐dose treatment (0 %, 31 %, 13 % vs. 21 %, 33 %, 20 % at days 4, 11, and 25 after normal and high dose, respectively). Including ret% as a stand‐alone marker for atypical blood profiles increased (P < 0.05) the sensitivity of the adaptive model at day 11 to 63 % and 67 % for normal‐dose and high‐dose rHuEPO administration, respectively. In conclusion, 30 % of subjects injecting a normal‐dose rHuEPO for two weeks or a high‐dose rHuEPO for three days will present an atypical ABP profile. Including ret% as a stand‐alone parameter improves the sensitivity two‐fold. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : The effect of low‐dose rHuEPO for two weeks or high‐dose rHuEPO for three days on the Athlete Biological Passport and reticulocyte percentage was evaluated. The Athlete Biological Passport is capable of identifying 30 % of the treated subjects using haemoglobin concentration or OFF‐hr score. The sensitivity is, however, increased two‐fold when the reticulocyte percentage is added as a stand‐alone marker.